Characterization of long period gratings manufactured with fiber optic fusion splicer for sensor development - Alustiza, Diego Horacio (2020)
A Long Period Grating (LPG) is a structure inscribed in an optical fiber that is of great interest in the field of communications and sensors. At Centro de Investigaciones Ópticas (CIOp), an LPG manufacturing process was implemented. It is based on use of electric arcs produced with an optical fiber splicer to generate a series of physical disturbances that modify optical fiber behavior as a light transmission guide. Since transmission response of LPG is sensitive to fiber environment conditions, it can be used to detect changes in certain physical and chemical parameters. In particular, it enables the implementation of optical sensors sensitive to temperature, surrounding medium refractive index and axial deformation. Characterization of locally generated LPGs is essential for future design of sensors applicable in many engineering areas. In this article, typical LPG sensitivities to the three mentioned parameters are reported